2014
DOI: 10.1055/s-0034-1365108
|View full text |Cite
|
Sign up to set email alerts
|

Acute colonic intramural hematoma: a rare complication of colonoscopy

Abstract: Acute colonic intramural hematoma: a rare complication of colonoscopyA 74-year-old man with a medical history of chronic renal failure and congestive heart failure underwent diagnostic colonoscopy following a positive fecal occult blood test. He was given oral antiplatelet medications including aspirin (100 mg/ day) and sarpogrelate hydrochloride (100 mg/day), which were stopped 5 days before colonoscopy. During the procedure, difficulty was encountered in reaching the ileocecal valve because of a redundant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In cases of intramural hematoma after diagnostic colonoscopy without polypectomy, the patients noticed hematochezia 6 and 12 hours after the procedure, and in one case, hematoma was noticed during the same colonoscopy on withdrawal. 7 Our patient presented with hematochezia 72 hours after the colonoscopy. Unlike in other described cases, abdominal pain was not present in our case.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In cases of intramural hematoma after diagnostic colonoscopy without polypectomy, the patients noticed hematochezia 6 and 12 hours after the procedure, and in one case, hematoma was noticed during the same colonoscopy on withdrawal. 7 Our patient presented with hematochezia 72 hours after the colonoscopy. Unlike in other described cases, abdominal pain was not present in our case.…”
Section: Discussionmentioning
confidence: 80%
“…9 A similarity between our case and those published in the literature is that more than half of the patients with intramural hematoma were taking antithrombotic agents. 2,4,6,7,9…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced CT (CECT) along with colonoscopy is the modality of choice for diagnosis of colonic intramural hematoma. 13 It has been suggested that non-contrast CT should be performed for oral and intravenous contrast medium application, as contrast-enhanced CT alone may mask the presence of intramural hemorrhage. 6 Computed tomography diagnostic criteria of colonic hematomas include eccentric or circumferential wall thickening, intramural hyper-density, narrowing of the lumen and intestinal obstruction, as shown in Figure 1 .…”
Section: Diagnosis and Complicationsmentioning
confidence: 99%
“… 25 Although an intramural hematoma can be primarily associated with an invasive endoscopic procedure, including biopsy or therapeutic procedures, an incidence of spontaneous intramural hematomas during a diagnostic colonoscopy has been reported in a few cases. 13 …”
Section: Endoscopic Managementmentioning
confidence: 99%
“…An intramural hematoma of the gastrointestinal tract could be precipitated by an endoscopic examination, especially in patients being administered anticoagulation therapy or those with concomitant hematological diseases [ 1 ]. Although an intramural hematoma can be primarily associated with a biopsy or therapeutic procedure, occurrence of a spontaneous intramural hematoma during a diagnostic colonoscopy has been reported in a few cases [ 2 - 4 ]. Intramural hematomas are known to cause partial or complete bowel obstruction [ 5 ], and surgical treatment should be considered in patients with evidence of intestinal necrosis, peritonitis, or a deteriorating general condition despite conservative management [ 6 , 7 ].…”
mentioning
confidence: 99%